Entrepreneurship Education and Entrepreneurial Intention: The Moderating Roles of Financial and Entrepreneurial Literacy in Higher Education - Hasyim, Sitti Hajerah; Isma, Andika; Dewantara, Hajar; Diarra, Salim (Quantitative Economics and Management Studies, 2025)
This study investigates whether and how entrepreneurship education (EE) shapes university students’ entrepreneurial intention (EI) in Makassar, Indonesia, focusing on the roles of financial literacy (FL) and entrepreneurial literacy (EL). We conducted a cross-sectional survey of students who had taken entrepreneurship-related courses. Regression-based path analysis was used to estimate direct effects from EE to EI and to test capability-building links from EE to FL and EL. We examined both indirect (mediation) effects via FL and EL using bootstrapped estimates and the conditional (moderation) influence of FL and EL on the EE→EI relationship. EE exerts a positive and significant direct effect on EI (β = 0.276, p < .001). EE also predicts higher levels of FL and EL, and each literacy is positively associated with EI. Indirect-effect tests indicate partial mediation: EE increases EI in part because it builds FL and EL, which subsequently elevate intention. In addition, higher levels of FL and EL strengthen the EE→EI link, consistent with a conditional (moderation) role for these literacies. EE is most impactful when it is competence-rich. Embedding structured financial planning, market validation, and venture design practices into EE—paired with authentic assessments (e.g., pro formas, MVPs, incubator sprints)—should yield larger gains in EI than theory-only formats. By jointly modeling capability-building (mediation) and capability-amplifying (moderation) roles of FL and EL, this study clarifies how and when EE translates into stronger entrepreneurial intention in an emerging-market higher-education context.